Ghanaians Might Be at Risk of Excess Dietary Intake of Potassium Based on Food Supply Data. (17th October 2018) - Yawson, David Oscar; Adu, Michael Osei; Ason, Benjamin; Armah, Frederick Ato; Boateng, Emmanuel; Quansah, Reggie
Abstract : The World Health Organization (WHO) has highlighted the beneficial role of adequate intake of potassium (K) in combating the global burden of noncommunicable diseases (NCDs), mainly hypertension and cardiovascular diseases. Diets are the main source of K supply to humans and can contribute to both K deficiency (hypokalemia) and excess (hyperkalemia). While global attention is currently devoted to K deficiency, K excess can be even more dangerous and deserves equal attention. The objectives of this paper were to (i) estimate the K intake of Ghanaian population using food supply and food composition data and (ii) compare this estimate with the WHO-recommended requirement for K in order to assess if there is a risk of inadequate or excess K intake. Food supply data (1961–2011) were obtained from the Food Balance Sheet (FBS) of the Food and Agriculture Organization of the United Nations to derive trends in food and K supply. The average food supply in the FBS for 2010 and 2011 was used in assessing the risk of inadequate or excess dietary intake of K. The K content of the food items was obtained from food composition databases. Based on 2010-2011 average data, the K supply per capita per day was approximately 9, 086 mg, about 2.6-fold larger than the WHO-recommended level (3, 510 mg). The assessment suggests a potentially large risk of excess dietary K supply at both individual and population levels. The results suggest the need for assessing options for managing K excess as part of food security and public health strategies. The results further underscore a need for assessment of the K status of staple food crops and mixed diets, as well as K management in food crop production systems in Ghana.